1998
DOI: 10.1677/joe.0.1560237
|View full text |Cite
|
Sign up to set email alerts
|

Gastric inhibitory polypeptide and effects of glycation on glucose transport and metabolism in isolated mouse abdominal muscle

Abstract: This study investigates the effects of gastric inhibitory polypeptide (GIP) and glycated GIP (glucitol adduct of GIP) on glucose uptake and metabolism in muscle. Glycated GIP (molecular mass 5147·2 Da) was purified by HPLC following in vitro incubation under hyperglycaemic reducing conditions (24 h at pH 7·4). GIP (10 10

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 36 publications
(30 reference statements)
2
31
0
Order By: Relevance
“…In contrast, (Gly 2 )GIP demonstrated a significantly improved insulin-releasing activity compared with the native peptide. These observations may also indicate that extrapancreatic actions (Elahi et al 1986, O'Harte et al 1998a) may be particularly important in mediating effects of (Ser 2 )GIP. Overall, these in vivo results confirm the predictions that these DPP IV-resistant Ala 2 -substituted analogues of GIP exhibit increased biological potency and antihyperglycaemic activity in type 2 diabetes with -cell dysfunction.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In contrast, (Gly 2 )GIP demonstrated a significantly improved insulin-releasing activity compared with the native peptide. These observations may also indicate that extrapancreatic actions (Elahi et al 1986, O'Harte et al 1998a) may be particularly important in mediating effects of (Ser 2 )GIP. Overall, these in vivo results confirm the predictions that these DPP IV-resistant Ala 2 -substituted analogues of GIP exhibit increased biological potency and antihyperglycaemic activity in type 2 diabetes with -cell dysfunction.…”
Section: Discussionmentioning
confidence: 93%
“…In addition to actions on the pancreatic -cell, GIP is also known to exert various extrapancreatic effects, which further promote glucose lowering. Thus, GIP has been shown to augment insulindependent inhibition of glycogenolysis in liver (Elahi et al 1986) and to exert stimulatory effects on glucose uptake and metabolism in muscle (O'Harte et al 1998a). Furthermore, functional GIP receptors have been identified on adipocytes (Yip et al 1998) and have been shown to stimulate glucose transport (Eckel et al 1979), increase fatty acid synthesis (Oben et al 1991) and stimulate lipoprotein lipase activity (Knapper et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…6. These actions include effects on hexose transport in the intestine (Tseng et al 1999) or actions on liver, muscle or adipose tissue (O'Harte et al 1998, Yip & Wolfe 2000, Rudovich et al 2004). However, it may be possible that the reduction in basal plasma glucose concentrations by daily GIP(3-42) treatment led to reduced glucose toxicity in these animals and thus contributed to the improvement of their diabetic status.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these incretin hormones have been reported to have other beneficial effects on b-cells, including stimulation of proliferation and neogenesis and inhibition of apoptosis (Buteau et al 1999, Trumper et al 2002, Ehses et al 2003. Various extrapancreatic actions have been suggested, such as stimulation of glucose uptake and metabolism (Villanueva-Penacarrillo et al 1994, O'Harte et al 1998 and inhibition of hepatic insulin extraction (Trapote et al 1996, Rudovich et al 2004). In addition, GIP has been reported to affect the aspects of lipid metabolism, whereas a key effect of GLP-1 is inhibition of gastric emptying (Nauck 1999, Yip & Wolfe 2000.…”
Section: Introductionmentioning
confidence: 99%
“…The GIP receptor is expressed in various extrapancreatic sites, including adipose tissue, bone, intestine, heart, stomach and brain [20]. In relation to this, GIP has been shown to inhibit gastric acid secretion [21], attenuate glucagon-stimulated glucose production [22], decrease hepatic insulin extraction [23] stimulate glucose uptake in muscle [24] and increase both fatty acid synthesis and lipoprotein lipase activity in adipocytes [25,26]. The particularly potent stimulation of GIP secretion after high-fat feeding [27] suggests a role for GIP in fat metabolism [20].…”
Section: Introductionmentioning
confidence: 99%